CIMAS Student Feedback Survey Report - Leslie Abell::::::
CSUCI Initiative for Mapping Academic Success (CIMAS) was designed to increase student retention and help maintain students' progress toward graduation. This initiative was largely based on an Excelencia in Education "Program to Watch" commended program designed by CSUCI Sociology faculty in partnership with Academic Advising, yet it was expanded in scope and support.